Patterns of culture - Benedict, Ruth, 1887-1948. (Boston : Houghton Mifflin, 1989)
A study of three contrasting cultures --the Pueblos of New Mexico, the natives of Dobu in Melanesia, and the Indian tribes of the American Northwest coast.
Includes index.
Bibliography: p. [279]-[286].
Notable/Best Books (A.L.A.).
Wilson's Senior High School.
Young Adult
Keywords: Culture; Ethnology -- Papua New Guinea -- Dobu Island; Ethnopsychology; Kwakiutl Indians; Zuni Indians; Culture; Ethnology -- Dobu Island (Papua New Guinea); Kwakiutl Indians; Zuni Indians; Dobu Island (Papua New Guinea) -- Social life and customs